Drug Survival of Interleukin (IL)‑17 and IL‑23 Inhibitors for the Treatment of Psoriasis: A Retrospective Multi‑country, Multicentric Cohort Study - Torres, Tiago; Puig, Luis; Vender, Ron; Yeung, Jensen; Carrascosa, José-Manuel; Piaserico, Stefano; Gisondi, Paolo; Lynde, Charles; Ferreira, Paulo; Bastos, Pedro Mendes; Dauden, Esteban; Leite, Luiz; et al. (American journal of clinical dermatology, 2022)
BACKGROUND: Drug survival, defined as the length of time from initiation to discontinuation of a given therapy, allows comparisons between drugs, helps to predict patient's likelihood of remaining on a specific treatment, and achieving the best decision for each patient in daily clinical practice. OBJECTIVE: The aim of this study was to provide data on drug survival of secukinumab, ixekizumab, brodalumab, guselkumab, tildrakizumab, and risankizumab in a large international cohort, and to identify clinical predictors that might have an impact on the drug survival of these drugs. METHODS: This was a retrospective, multicentric, multi-country study that provides data of adult patients with moderate to severe psoriasis who started treatment with an interleukin (IL)-17 or IL-23 inhibitor between 1 February 2015 and 31 October 2021. Data were collected from 19 distinct hospital and non-hospital-based dermatology centers from Canada, Czech Republic, Italy, Greece, Portugal, Spain, and Switzerland. Kaplan-Meier estimator and proportional hazard Cox regression models were used for drug survival analysis. RESULTS: A total of 4866 treatment courses (4178 patients)-overall time of exposure of 9500 patient-years-were included in this study, with 3164 corresponding to an IL-17 inhibitor (secukinumab, ixekizumab, brodalumab) and 1702 corresponding to an IL-23 inhibitor (guselkumab, risankizumab, tildrakizumab). IL-23 inhibitors had the highest drug survival rates during the entire study period. After 24 months of treatment, the cumulative probabilities of drug survival were 0.92 (95% confidence interval [CI] 0.89-0.95) for risankizumab, 0.90 (95% CI 0.88-0.92) for guselkumab, 0.80 (95% CI 0.76-0.84) for brodalumab, 0.79 (95% CI 0.76-0.82) for ixekizumab, and 0.75 (95% CI 0.73-0.77) for secukinumab. At 36 months, only guselkumab [0.88 (95% CI 0.85-0.91)], ixekizumab [0.73 (95% CI 0.70-0.76)], and secukinumab [0.67 (95% CI 0.65-0.70)] had more than 40 patients at risk of drug discontinuation. Only two drugs had more than 40 patients at risk of drug discontinuation at 48 months, with ixekizumab demonstrating to have a higher cumulative probability of drug survival [0.71 (95% CI 0.68-0.75)] when compared with secukinumab [0.63 (95% CI 0.60-0.66)]. Secondary failure was the main cause for drug discontinuation. According to the final multivariable model, patients receiving risankizumab, guselkumab, and ixekizumab were significantly less likely to discontinue treatment than those receiving secukinumab. Previous exposure to biologic agents, absent family history of psoriasis, higher baseline body mass index (BMI), and higher baseline Psoriasis Area and Severity Index (PASI) were identified as predictors of drug discontinuation. CONCLUSION: The cumulative probability of drug survival of both IL-17 and IL-23 inhibitors was higher than 75% at 24 months, with risankizumab and guselkumab demonstrating to have overall cumulative probabilities ≥ 90%. Biological agent chosen, prior exposure to biologic agents, higher baseline BMI and PASI values, and absence of family history of psoriasis were identified as predictors for drug discontinuation. Risankizumab, guselkumab, and ixekizumab were less likely to be discontinued than secukinumab.
Keywords: Psoriasis; Humans; stupeň závažnosti nemoci; retrospektivní studie; Interleukin-17; Adult; interleukin-23; Severity of Illness Index; inhibitory interleukinu; Interleukin Inhibitors; výsledek terapie; lidé; Retrospective Studies; psoriáza; dospělí; Treatment Outcome; interleukin-17; Interleukin-23